2021
DOI: 10.3390/children8090752
|View full text |Cite
|
Sign up to set email alerts
|

Results of COVID-19 Surveillance in a Large United States Pediatric Healthcare System over One Year

Abstract: Background: The lack of SARS-CoV-2 antigen surveillance testing in the pediatric population has inhibited accurate infection and hospitalization prevalence estimates. We aim to report the estimated prevalence of and risk factors for COVID-19 infection, hospitalization, and intensive care unit (ICU) admission across the three United States (US) waves in one of the largest pediatric healthcare systems in the nation. Methods: Retrospective electronic health record (EHR) review of all COVID-19 surveillance data am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…A higher hospitalization rate for children with infection of Omicron variants was initially reported from Gauteng Province, South Africa, where 462 (18%) of hospitalizations were patients less than 19 years of age, higher than those in the three previously pandemic waves [32]. In two larger cohort studies of COVID-19 in children found that hospitalized children aged < 2 years or with comorbidities were susceptible to severe COVID-19 and potential fatality [1,2,33,34]. Higher severity and fatality of non-pulmonary disease have been later found in Hong Kong and Taiwan where the Omicron BA.2 was prevalent [14,15].…”
Section: Dynamic Changes From Pulmonary To Inflammatory Non-pulmonary...mentioning
confidence: 92%
See 2 more Smart Citations
“…A higher hospitalization rate for children with infection of Omicron variants was initially reported from Gauteng Province, South Africa, where 462 (18%) of hospitalizations were patients less than 19 years of age, higher than those in the three previously pandemic waves [32]. In two larger cohort studies of COVID-19 in children found that hospitalized children aged < 2 years or with comorbidities were susceptible to severe COVID-19 and potential fatality [1,2,33,34]. Higher severity and fatality of non-pulmonary disease have been later found in Hong Kong and Taiwan where the Omicron BA.2 was prevalent [14,15].…”
Section: Dynamic Changes From Pulmonary To Inflammatory Non-pulmonary...mentioning
confidence: 92%
“…Coronavirus disease 2019 (COVID-19) has evolved from initial waves of mild pulmonary diseases to the later waves of potentially fatal diseases of non-pulmonary encephalopathies, and multisystem inflammatory syndrome in children (MIS-C) [1][2][3][4]. The evolutional variants of SARS-CoV-2 have caused immune escapes of vaccines and monoclonal antibodies, resulting in incomplete herd immunity and periodic re-emergence [5,6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the UK, shielding meant not leaving one’s home under any circumstances unless seeking urgent medical care, and whilst pregnant women were eventually declassified from this level of vulnerability, it has been found that third trimester COVID-19 infection causes worsened maternal symptomatology [ 18 ]. Subsequent evidence countered the precautionary measures given for pregnant women to shield–finding limited evidence for vertical transmission between mother and infant [ 19 ], and mild presentation of symptoms in a large proportion of infected infants [ 20 ]. Despite which, separation of infected mothers and infants was still routinely practiced in some NHS settings at this time [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Population prevalence of SARS-CoV-2 exposure is an important factor for understanding the effectiveness of control methods and predicting the susceptibility of a given population to future outbreaks. Lack of data on SARS-CoV-2 exposure in children has contributed to inaccurate population prevalence estimates [3]. This is due to several factors, such as the lack of testing supplies and access to a large ambulatory pediatric cohort and the fact that COVID-19 is generally mild in children.…”
Section: Introductionmentioning
confidence: 99%